Unraveling Alice: a psychoanalytic analysis of the Wonderland - Oliveira, Flávia Cristina Martins (2018)
The author decided to write this article because of her questions about the story Alice in Wonderland. Lewis Carroll, when presenting Alice’s oneiric world, invites the reader to enter in her intimacy, and in this way, he can dive in the dream of this brave, curious and determined girl. With the studies of the psychoanalytic theories, the author had the opportunity of analyzing this book under the freudian theory. Freud, with his work The Interpretation of Dreams, is able to proof the existence of the unconsciousness. Everything that is lived, experienced, affects the subject psychically, being in constant construction. Awake, the subjects use their ego and superego to realize their daily functions. Sleeping, they dream to release their id, relieving their pressures and giving space to the unconscious. During the analysis of the book, Alice in her oneiric adventures, sees herself lost in a strange world that she makes effort to understand. Through her path she gets stronger, having control of what she wants to do and to say. It is realized a consolidation of her psychic structure when she meets other characters. It is with the meeting of her own unconscious that she becomes brave and decided.